A Readily Accessible Functional Nanofibrous Membrane for High‐Capacity Immobilization of Ag Nanoparticles and Ultrafast Catalysis Application. Issue 5 (28th December 2018) - Liu, Ke; Cheng, Pan; Kong, Chuncai; Guo, Qihao; Lu, Zhentan; Liu, Qiongzhen; Li, Mufang; Wang, WenWen; Wang, Yuedan; Zhong, Weibing; Sun, Gang; Wang, Dong
Abstract: Constructing macroscopic materials with optimal surface structure to immobilize silver nanoparticles polluted in water environment and further maximize their practical functionality still remains a great challenge. An infrequent strategy is developed to build a flexible material system combining PVA‐ co ‐PE nanofiber membrane (NFM) scaffold and mussel‐inspired polydopamine (PDA), which provides a formidable surface interacting with polyethyleneimine (PEI). The resultant PEI/PDA/NFM presents an ultrahigh adsorption capacity (727.8 mg g −1 ) to citrate‐capped silver nanoparticles much higher than the values reported in the literatures. The broad applicability of the multifunctional composite membranes in water treatment is further demonstrated. Interestingly, a promising concurrent performance of antibacterial, antifouling, and catalysis is acquired in bacterial filtrations. Benefiting from the structure, a plasma process further enhances the catalytic performance of AgNPs‐PEI/PDA/NFM with an ultrahigh turnover frequency value: 6.65 × 10 −1 mol mol −1 min −1, which facilitates the fast degradation treatment of p ‐nitrophenol ( p ‐NP) in continuous‐flow filtration. The excellent properties can be rationally assigned to the optimized surface structure synergistically determined by the high specific area of porous nanofiber scaffold and high substrate adaptability of reactive polydopamine. This implies the superiority of membranes obtained by present strategy in recycling Ag NPs contaminant and further applies it in fast‐efficient wastewater treatment applications. Abstract : A superhigh‐capability immobilized Ag nanoparticle is achieved by synergistical optimization of surface structure in PVA‐ co ‐PE nanofiber scaffold and polydopamine materials system. The resultant flexible porous composite membrane presents fast and recycled catalysis performance after oxygen plasma treatment, implying superiority in the related environmental treatment.